How do environmental factors influence life cycles and development? An experimental framework for early‐diverging metazoans. (10th September 2014) - Bosch, Thomas C. G.; Adamska, Maja; Augustin, René; Domazet‐Loso, Tomislav; Foret, Sylvain; Fraune, Sebastian; Funayama, Noriko; Grasis, Juris; Hamada, Mayuko; Hatta, Masayuki; Hobmayer, Bert; Kawai, Kotoe; et al.
<x xml:space="preserve">Abstract</x> Ecological developmental biology (eco‐devo) explores the mechanistic relationships between the processes of individual development and environmental factors. Recent studies imply that some of these relationships have deep evolutionary origins, and may even pre‐date the divergences of the simplest extant animals, including cnidarians and sponges. Development of these early diverging metazoans is often sensitive to environmental factors, and these interactions occur in the context of conserved signaling pathways and mechanisms of tissue homeostasis whose detailed molecular logic remain elusive. Efficient methods for transgenesis in cnidarians together with the ease of experimental manipulation in cnidarians and sponges make them ideal models for understanding causal relationships between environmental factors and developmental mechanisms. Here, we identify major questions at the interface between animal evolution and development and outline a road map for research aimed at identifying the mechanisms that link environmental factors to developmental mechanisms in early diverging metazoans. Also watch the Video Abstract.